2018
DOI: 10.1093/ecco-jcc/jjy112
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Insulin Instillation Inhibits Inflammation and Tumor Development in Chemically Induced Colitis

Abstract: Rectal insulin therapy could potentially be a novel treatment, targeting the epithelial layer to enhance mucosal healing in ulcerated areas. Our findings open up new possibilities for combination treatments to synergize with the existing anti-inflammatory therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…More recently, investigated sugar-induced exacerbation of colitis when adding 10% glucose or fructose in drinking water (mimicking sugar-sweetened beverages), dietary sugars quickly altered gut microbial ecology ( 13 ). In agreement with these findings, rectal insulin instillation inhibited inflammation in chemically-induced colitis in mice ( 14 ). Although growing evidence underpins the pro-inflammatory effect of sugars ( 15 , 16 ), the long-term impact of combined excessive intake of dietary sugar and fat due to ultra-processed food overconsumption (enriched in added sugars) on healthy intestine and the underlying molecular mechanisms remain poorly described ( 9 ).…”
Section: Introductionsupporting
confidence: 69%
“…More recently, investigated sugar-induced exacerbation of colitis when adding 10% glucose or fructose in drinking water (mimicking sugar-sweetened beverages), dietary sugars quickly altered gut microbial ecology ( 13 ). In agreement with these findings, rectal insulin instillation inhibited inflammation in chemically-induced colitis in mice ( 14 ). Although growing evidence underpins the pro-inflammatory effect of sugars ( 15 , 16 ), the long-term impact of combined excessive intake of dietary sugar and fat due to ultra-processed food overconsumption (enriched in added sugars) on healthy intestine and the underlying molecular mechanisms remain poorly described ( 9 ).…”
Section: Introductionsupporting
confidence: 69%
“…Note that to avoid the influences of abundant gastrointestinal proteinase and peptidase, we directly injected these purified proteins to the colons of HFD-fed mice according to a previous study. 29 Because M. timonae is the corresponding bacteria of GSDMD-N proteins, we firstly examined the abundance of M. timonae every 2 days. We found that the abundance of M. timonae from the feces of HFD-fed mice treated with GSDMD-N WT were significantly decreased to 41% at day 10, when compared to the control group ( Figure 5(a,b) ).…”
Section: Resultsmentioning
confidence: 99%
“…Such switchers may be affected by previous therapydfor example, physicians may switch patients on metformin or glucagon-like peptide 1 receptor agonists to DPP4i due to development of gastrointestinal symptoms (which may be either drug adverse events [33] or early symptoms of IBD). Notably, in a head-to-head comparison of the CPRD study, a higher risk was also observed comparing DPP4i versus insulin (HR 2.28 [1.07-4.85]), which might be due to a speculative potential protective effect of insulin on UC (34).…”
Section: Comparison With Previous Studiesmentioning
confidence: 98%